2021
DOI: 10.3389/fonc.2021.743780
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Modulation by Viral Infections Influences Tumor Development

Abstract: Autophagy is a self-degradative process important for balancing cellular homeostasis at critical times in development and/or in response to nutrient stress. This is particularly relevant in tumor model in which autophagy has been demonstrated to have an important impact on tumor behavior. In one hand, autophagy limits tumor transformation of precancerous cells in early stage, and in the other hand, it favors the survival, proliferation, metastasis, and resistance to antitumor therapies in more advanced tumors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 238 publications
(255 reference statements)
0
6
0
Order By: Relevance
“…Shi et al, (2016) reported that knocking out HMGA2 increased the expression of pro-apoptotic genes Bax and reduced cell proliferation, indicating the anti-apoptotic ability of HMGA2 in cancer cells. A recent study by Leonardi et al, (2021) reported that CDK was dysregulated during virus infection to bypass the cell cycle in tumorigenesis. Thus, our target genes are consistent with enrichment in response to viruses and G1/S and G2/M transition of mitotic cell cycles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shi et al, (2016) reported that knocking out HMGA2 increased the expression of pro-apoptotic genes Bax and reduced cell proliferation, indicating the anti-apoptotic ability of HMGA2 in cancer cells. A recent study by Leonardi et al, (2021) reported that CDK was dysregulated during virus infection to bypass the cell cycle in tumorigenesis. Thus, our target genes are consistent with enrichment in response to viruses and G1/S and G2/M transition of mitotic cell cycles.…”
Section: Discussionmentioning
confidence: 99%
“…KPNA4 is a nuclear import protein that is vital in promoting malignant phenotypes in LUAD cells (Hu et al, 2020). Both KPNA4 and KPNB1 were enriched in the modulation of the virus-mediated host process, and autophagy has been reported to influence tumour behaviour, especially at the early stages of oncogenesis (Leonardi et al, 2021). KARS encodes aminoacyl-tRNA synthetase, which is required for mRNA translation and has become a target of autoantibodies in autoimmune diseases (Vargas et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, what is interesting is that when a pathogen infects, autophagy is initiated to eliminate the pathogen. During virus replication, autophagy is activated to complete the replication of viruses by maintaining the state of the cell [ 52 ]. From the perspective of pathogens, it would be interesting to see how autophagy affects infections.…”
Section: Viruses Interacting With Cell Surface Receptors Triggering A...mentioning
confidence: 99%
“…Microautophagy refers to invagination of the lysosomal membrane for the phagocytosis of cytoplasmic substrates. Macroautophagy is characterized by the formation of autophagosomes with a double‐layered membrane structure; these autophagosomes fuse with lysosomes to form autophagolysosomes, which degrade and recycle the phagocytosed substances 99,100 . Macroautophagy is the most common form of autophagy (hereinafter, macroautophagy is referred to as autophagy); it can be activated by unc‐51‐like autophagy activating kinase 1 (ULK 1), ULK 2, autophagy‐related protein 13 (Atg13) and Beclin‐1/III PI3K complexes.…”
Section: Inflammation Cell Death and Glial Scar Formation In Secondar...mentioning
confidence: 99%
“…Macroautophagy is characterized by the formation of autophagosomes with a double-layered membrane structure; these autophagosomes fuse with lysosomes to form autophagolysosomes, which degrade and recycle the phagocytosed substances. 99,100 Macroautophagy is the most common form of autophagy (hereinafter, macroautophagy is referred to as autophagy); it can be activated by unc-51-like autophagy activating kinase 1 (ULK 1), ULK 2, autophagy-related protein 13 (Atg13) and Beclin-1/III PI3K complexes. When autophagy is activated, these complexes recruit other proteins involved in the extension and formation of autophagosomes (e.g., Atg12, Atg5, Atg16L and light chain 3 [LC3]) to form conjugate complexes.…”
Section: Cell Deathmentioning
confidence: 99%